Impact of seaweed beachings on dynamics of δ15N isotopic signatures in marine macroalgae. Issue 1 (15th August 2015) - Lemesle, Stéphanie; Mussio, Isabelle; Rusig, Anne-Marie; Menet-Nédélec, Florence; Claquin, Pascal
Highlights: Two coastal sites (COU, GM) in the Bay of Seine affected by summer seaweed beachings. The same temporal dynamics of the algal δ 15 N at the two sites. N and P concentrations in seawater of the two sites dominated by riverine sources. A coupling between seaweed beachings and N sources of intertidal macroalgae. Abstract: A fine-scale survey of δ 15 N, δ 13 C, tissue-N in seaweeds was conducted using samples from 17 sampling points at two sites (Grandcamp-Maisy (GM), Courseulles/Mer (COU)) along the French coast of the English Channel in 2012 and 2013. Partial triadic analysis was performed on the parameter data sets and revealed the functioning of three areas: one estuary (EstA) and two rocky areas (GM ∗, COU ∗ ). In contrast to oceanic and anthropogenic reference points similar temporal dynamics characterized δ 15 N signatures and N contents at GM ∗ and COU ∗ . Nutrient dynamics were similar: the N-concentrations in seawater originated from the River Seine and local coastal rivers while P-concentrations mainly from these local rivers. δ 15 N at GM ∗ were linked to turbidity suggesting inputs of autochthonous organic matter from large-scale summer seaweed beachings made up of a mixture of Rhodophyta, Phaeophyta and Chlorophyta species. This study highlights the coupling between seaweed beachings and nitrogen sources of intertidal macroalgae.